A comparative study of placental abnormalities in normal and specific high-risk pregnancies by using Doppler, histology and their fetal outcome - Dikshamani; Sharma, Indu; Dhruw, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The placenta, a vital organ connecting mother and fetus, undergoes significant growth and facilitates essential exchange. Various placental pathologies, including issues with vascular processes, inflammation, and structural abnormalities, can impact pregnancy outcomes. Conditions like placenta accreta, placenta previa, and vasa previa pose significant risks. Diagnosis and evaluation of these abnormalities are primarily done through ultrasound imaging, doppler ultrasound for blood flow assessment, and histopathology after birth. Methods: This two-year prospective observational study at Lt. Baliram Kashyap Memorial Govt. Medical College will investigate placental characteristics in 200 pregnant women (100 normal, 100 high-risk) over 28 weeks’ gestation. It involves detailed examination of placentas and babies, with data analyzed using SPSS. The study has ethical approval and aims to identify associations between placental features and pregnancy outcomes. Results: In this study of 200 pregnant women, high-risk pregnancies were associated with older maternal age (mean 26.5 vs 24.6 years, p<0.01) and a higher proportion of multiparous women (p<0.01). Key placental abnormalities (round shape, infarct, fibrosis) and umbilical cord abnormalities (edema, foul-smelling liquor) were significantly more prevalent in the high-risk group. Doppler findings showed that an abnormal Systolic/Diastolic ratio was significantly linked to adverse perinatal outcomes. Overall, various maternal and fetal factors contribute to high-risk pregnancies and their associated complications. Conclusions: Placental abnormalities (infarcts, fibrosis, bleeding) and umbilical cord issues (edema, foul-smelling liquor, marginal insertion) are major indicators of high-risk pregnancies and poor neonatal outcomes. Conditions like pre-eclampsia and gestational hypertension also correlate with these placental issues. Early ultrasound and Doppler studies are crucial for detection, necessitating increased clinical caution in managing such pregnancies. Further research is vital to establish comprehensive guidelines for improved care.